Using the Body as a Medium to Practice Digital Health Literacy: Exploration of Attention Grabber for Self-Health Management of Urban Fitness Youth - Huang, Junyang; Gao, Zhenghan; Liu, Jiatai (The Journal of Medicine, Humanity and Media, 2025)
With the rise and popularization of wearable devices in the digital intelligence era, sports bracelets have become a concrete reality carrier of digital health literacy by presenting functions such as body data, information sharing and communication, and community emotional connection. This paper uses questionnaire survey, in-depth interview and field survey method to study the deep reasons why sports bracelets can lead the new trend of urban fitness youth, and how to empower this group of people to use digital health management as a mediator. The results show that the sports bracelet plays a role in psychological boost, emotional connection and media discipline in the process of self-health management of urban fitness youth, simplifying the way of obtaining health information and mobilizing their enthusiasm for self-health management. However, the data constraints caused by the transparency of tools will also weaken users' autonomy in health management and break the co-shaping relationship. In addition, as a smart wearable device, the sports bracelet will also cause a series of digital technology concerns such as data leakage, data comparison and error.